Adverse effect of consumption of carbonated soft drinks on orthodontic treatment - A systematic review - Keerthi Venkatesan; Bhadrinath Srinivasan; Sridevi Padmanabhan (Wolters Kluwer Medknow Publications, 2021)
Introduction: The complications of soft drink consumption during orthodontic treatment includes degradation of enamel, reduction in the shear bond strength of orthodontic brackets, and also corrosion of orthodontic wires. The main objective of this review is to discuss the adverse effects of carbonated soft drink (CSD) consumption on patients undergoing fixed orthodontic treatment. Methods: A search of studies in MEDLINE (via PubMed), the Cochrane library, Web of science, IndMED, EMBASE, Google scholar and limited grey literature on the effects of consumption of CSDs was conducted. All pertinent abstracts were reviewed for inclusion. Full articles were retrieved for abstracts or titles that met the initial inclusion criteria or lacked sufficient detail for immediate exclusion. Results: Out of the 4484 results obtained from search, 16 articles were selected based on title and 6 articles were eliminated after reading the abstracts. 10 articles were selected for systematic review which included 6 invitro studies, 1 animal study, 1 observational study and 2 invivo studies. Of these, six studies evaluated the effects of carbonated drinks on the shear bond strength of brackets on enamel of which two evaluated the microhardness of enamel, two studies evaluated the mechanical and chemical properties of wires, one evaluated tooth movement and one study focussed on white spot lesions. The results from the selected articles showed that with the consumption of carbonated drinks, there was reduced shear bond strength of orthodontic brackets, altered enamel characteristics, alteration of mechanical and physical properties of orthodontic wires and decrease in rate of orthodontic tooth movement. Conclusion: Based on the available evidence, CSD consumption during orthodontic treatment definitely has an effect on orthodontic appliances, enamel and possibly on tooth movement.